2022
DOI: 10.1177/15579883221119931
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lifestyle on Sperm Function, Telomere Length, and IVF Outcomes

Abstract: Many risk factors can potentially influence sperm quality. Telomeres confer stability on the chromosome and their dysfunction has been implicated in conditions such as cancer, aging, and lifestyle. The impact of lifestyle on sperm cell telomeres is unclear. The objectives of this study were to evaluate the impact of lifestyle behaviors on telomere length in sperm and to follow the correlation with pregnancy outcomes in patients undergoing in vitro fertilization (IVF). In this prospective observational study, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Recent studies have suggested that lifestyle choices including drinking alcohol and coffee, exercising, and smoking contribute to the length of sperm telomeres. Atypical STL spermatozoa have not yet resulted in any successful pregnancies following IVF or ICSI, and the measurement of STL was not thought to be accurate in determining reproductive outcomes in ICSI cycles utilizing donor semen ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that lifestyle choices including drinking alcohol and coffee, exercising, and smoking contribute to the length of sperm telomeres. Atypical STL spermatozoa have not yet resulted in any successful pregnancies following IVF or ICSI, and the measurement of STL was not thought to be accurate in determining reproductive outcomes in ICSI cycles utilizing donor semen ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found a relationship between the aforementioned parameters and STL integrity ( 52 ). These lifestyle factors considerably increase the occurrence of ROS when paired with advanced age ( 53 , 54 ). Due to their repeated patterns and high guanine content, telomeres are particularly vulnerable to oxidative damage, which results in the formation of 8-oxo-2-deoxyguanosine (8-oxo-dG) ( 55 ).…”
Section: Effects Of Ros On Telomeresmentioning
confidence: 99%
“…As we have depicted in the above data, there are wide-ranging issues that can affect sperm function and health, which results in male infertility. Iatrogenic or hereditary causes are the well-accepted etiologies, and one of the biggest contributors to this failure is modifiable lifestyle influences [ 44 , 45 , 46 ]. Studies have informed that exposure to numerous lifestyle issues, including smoking, alcohol, obesity, illicit drugs, fast food intake, caffeine and diet, can negatively affects male fertility [ 47 , 48 ].…”
Section: Impacts Of Lifestylementioning
confidence: 99%
“…Moreover, the drinking of alcohol may be associated with the male infertility by causing the Sertoli-cell syndrome, spermatogenic arrest and antioxidant imbalance due to high levels of seminal leucocytes [ 48 , 49 ]. Additionally, it has been mentioned that chronic alcohol consumption is further associated with epigenetic modulations and the transfer of these modifications to the next generation, which is evolving as a main cause of alcohol-related fetal growth blemishes via changed paternal DNA methylation [ 46 ]. In this regard, further clarifications are hunted to explore the transgenerational effects on the offspring health at the omics levels.…”
Section: Impacts Of Lifestylementioning
confidence: 99%
“…MRH is related to the erectile function, testicular functions of steroidogenesis (testosterone synthesis), and spermatogenesis, and it is influenced by numerous factors [ 3 , 4 ]. These factors include unhealthy eating habits, delayed marriage, exposure to environmental pollutants, psychological stress, drug abuse, and natural aging in humans [ 5 8 ]. Given the influence of traditional sexual concepts, many men are reluctant to admit that they have a reproductive disorder.…”
Section: Introductionmentioning
confidence: 99%